ANTIBACTERIAL DRUGS FOR RESPIRATORY INFECTIONS IN CHILDREN IN OUTPATIENT PRACTICE - Farmankulova Yorkinoy Rafikovna; Soliyeva Mavluda Odiljanovna (Scholar Express Journals, 2022)
Despite significant progress in the development of clinical pharmacology, the issues of the validity of prescribing medicines for acute respiratory infections remain relevant. The most important part of the pharmacotherapy of this pathology is the solution of the issue of the use of antibacterial drugs (ABP). Considering that the overwhelming majority of ARI (80-90%) have a viral etiology, the appointment of antibacterial drugs is justified only in rare cases: if there are irrefutable data confirming the presence of bacterial inflammation, or the probability of the latter is high according to clinical examination and laboratory examination
Keywords: Antibacterial treatment; pediatricians; multidirectional maladaptive effects; micro ecological system